Is production intensification likely to make farm households food-adequate? A simple food availability analysis across smallholder farming systems from East and West Africa - Ritzema, Randall S.; Frelat, Romain; Douxchamps, Sabine; Silvestri, Silvia; Rufino, Mariana C.; Herrero, Mario; Giller, Kenneth E.; López Ridaura, Santiago; Teufel, Nils; Paul, Birthe K.; Wijk, Mark T. van (Springer, 2017)
Despite considerable development investment, food insecurity remains prevalent throughout East and West Africa. The concept of ‘sustainable intensification’ of agricultural production has been promoted as a means to meet growing food needs in these regions. However, inadequate attention has been given to assessing whether benefits from intensification would be realized by farm households considering highly diverse resource endowments, household and farm characteristics, and agroecological contexts. In this study, we apply a simple energy-based index of food availability to 1800 households from research sites in 7 countries in East and West Africa to assess the food availability status of each of these households and to quantify the contribution of different on- and off-farm activities to food availability. We estimate the effects of two production intensification strategies on food availability: increased cereal crop production from crop-based options, and increased production of key livestock products from livestock-based options. These two options are contrasted with a third strategy: increased off-farm income for each household from broader socioeconomic-based options. Using sensitivity analysis, each strategy is tested against baseline values via incremental production increases. Baseline results exhibit considerable diversity within and across sites in household food availability status and livelihood strategies. Interventions represented in the crop and livestock options may primarily benefit food-adequate and marginally food-inadequate households, and have little impact on the most food-inadequate households. The analysis questions what production intensification can realistically achieve for East and West African smallholders, and how intensification strategies must be augmented with transformational strategies to reach the poorest households.